Peningkatan Pengetahuan Ibu Hamil tentang Prenatal Yoga melalui Edukasi dan Praktik di Puskesmas Tanjung Palas - Nurhidayati; Heni Setyowati; Novi Aryani (Universitas Ngudi Waluyo, 2025)
Pregnancy is a physiological process that often causes physical discomfort and psychological stress in pregnant women. Prenatal yoga is a non-pharmacological intervention that can improve physical comfort, reduce anxiety, and enhance maternal readiness for childbirth. However, pregnant women’s knowledge regarding prenatal yoga remains limited. This study aimed to determine the effect of health education on pregnant women’s knowledge about prenatal yoga. This study employed a pre-experimental design using a one-group pretest–posttest approach. The participants consisted of 10 pregnant women who attended a prenatal yoga health education program at the community health center area. Knowledge levels were measured using a structured questionnaire administered before (pretest) and after (posttest) the health education intervention. Data were analyzed descriptively and presented in the form of frequency distributions, tables, and diagrams. The results showed an improvement in pregnant women’s knowledge after receiving health education. Before the intervention, most respondents had insufficient to moderate knowledge regarding prenatal yoga. After the intervention, the majority of respondents demonstrated good knowledge. The increase was observed across all knowledge indicators, including the definition, benefits, appropriate timing, breathing techniques, safe movements, contraindications, and precautions during prenatal yoga practice.Health education significantly improved pregnant women’s knowledge about prenatal yoga. Therefore, prenatal yoga education is recommended to be routinely integrated into antenatal care programs to enhance maternal health and childbirth preparedness. Abstrak Kehamilan menyebabkan perubahan fisik dan psikologis yang sering menimbulkan keluhan pada ibu hamil. Prenatal yoga merupakan salah satu bentuk aktivitas fisik yang aman dan bermanfaat untuk meningkatkan kesehatan ibu hamil, namun tingkat pengetahuan ibu hamil tentang prenatal yoga masih beragam. Artikel ini bertujuan menganalisis pengaruh edukasi dan praktik prenatal yoga terhadap peningkatan pengetahuan ibu hamil. Penelitian ini merupakan kegiatan pengabdian kepada masyarakat dengan desain pre-eksperimental menggunakan pendekatan one group pre-test dan post-test. Subjek kegiatan adalah 10 ibu hamil trimester II dan III di wilayah kerja puskesmas. Intervensi berupa edukasi kesehatan, demonstrasi, dan praktik prenatal yoga. Pengukuran pengetahuan dilakukan menggunakan kuesioner terstruktur sebelum dan sesudah intervensi. Analisis data dilakukan secara deskriptif. Hasil pre-test menunjukkan sebagian besar responden memiliki tingkat pengetahuan kategori kurang dan cukup. Setelah diberikan edukasi dan praktik prenatal yoga, terjadi peningkatan pengetahuan dengan 90% responden berada pada kategori pengetahuan baik. Edukasi dan praktik prenatal yoga efektif dalam meningkatkan pengetahuan ibu hamil. Program prenatal yoga dapat dijadikan intervensi promotif dan preventif dalam pelayanan kesehatan ibu dan anak.